Analisis Kinerja Guru Kelas di Kecamatan Batu Berak Lampung Barat Tahun Pelajaran 2014/2015 - Darwin Bangun (Balitbangda Provinsi Lampung, 2015)
Homeroom teacher is a teacher who appointed to organize and make the classroom well managed. Classroom management basically is the process of teaching and learning process control activities that take place with dynamic, productive, effective and efficient so can create a harmonious circumstances. Homeroom teacher should have a very important function in classroom management. Homeroom teacher in classroom management take function as administrator and manager. In the other hand professional teacher is the a teacher’s ability to perform his core function as a educators and teachers ability to plan, actuate and evaluate the learning outcomes. Professional-level assessment process of a teacher can be measured from the teacher’s performances in carrying out his duties and responsibilities in the learning process. Performance is the success rate of a person or group in carrying out his duties and responsibilities and the ability to achieve the goals and standards that have been set. (Sulistyorini, 2001,2).